The Effect of Project Based Learning Model Assisted by Electronic Student Worksheet on Global Warming Material to Improve Creative Thinking Skills of Class X Students at SMA Negeri 2 Medan - Waruwu, Lilis Suryani; Motlan, Motlan (PILLAR OF PHYSICS EDUCATION, 2025)
The aim of this study was to determine whether there is an effect of using Project Based Learning model assisted by Electronic Student Worksheet (E-Worksheet) on students’ creative thinking skills in the global warning topic at Grade X of SMA Negeri 2 Medan. This research used a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 68 students of Grade X Phase E in the even semester at SMA Negeri 2 Medan, with 34 students in the experimental class and 34 students in the control class. Data collection was conducted using a creative thinking skills test based on four indicators: fluency, flexibility, originality, and elaboration. Data analysis included normality test, homogeneity test, and hypothesis testing. A one-tailed t-test on the post-test results showed that the t-count value of 3.761 exceeded the t-table value of 1.998, indicating a statistically significant difference between the experimental class was 82.79, higher than the control class average of 74.41. These results demonstrate that the implementation of the PjBL model assistes by E-Wroksheet significantly improves students’ creative thinking skills in learning global warming material compared to conventional learning methods.